Association between NMDAR antagonists, drug abuse and dependence: A disproportionality analysis from the WHO pharmacovigilance database. Issue 11 (14th June 2022) - Revol, Bruno; Lapeyre‐Mestre, Maryse; Fouilhé Sam‐Laï, Nathalie; Jouanjus, Emilie
Abstract : Ketamine and dextromethorphan are widely abused psychoactive substances. Inhibition of N‐methyl‐d‐aspartate receptors (NMDARs) results in neurobehavioural effects including hallucinations, "out of body" sensations and dissociative effects. However, little is known about a possible extended addictive class effect linked to pharmacologically‐related amino‐adamantane derivatives (e.g., amantadine and memantine). Using a quasi‐Bayesian analytic method, we investigated the potential association between the use of approved NMDAR antagonists (i.e., dextromethorphan, ketamine, amantadine and memantine) and the reporting of drug abuse and dependence in the WHO pharmacovigilance database (VigiBase®), which includes >21 million individual case safety reports collected from >130 countries. This disproportionality analysis identified a significant association for all investigated drugs: dextromethorphan (IC = 3.03 [2.97–3.09]), ketamine (IC = 1.70 [1.57–1.83]), amantadine (IC = 0.21 [0.06–0.35]) and memantine (IC = 0.27 [0.13–0.40]), suggesting a class effect for drug abuse and dependence. This first signal requires further investigations, but health professionals need to be alert to the potential of abuse of NMDAR antagonists, especially in the current "opioid epidemic" context, due to their growing interest as non‐opioid antinociceptive drugs.